Endoscopic versus microscopic transsphenoidal surgery in the treatment of pituitary tumors: Systematic review and meta-analysis of randomized and non-randomized controlled trials - Bastos, Rodrigo V. S. [UNESP]; Silva, Carla Maria D. M. [UNESP]; Tagliarini, Jose Vicente [UNESP]; Zanini, Marco Antonio [UNESP]; Romero, Flavio R. [UNESP]; Boguszewski, Cesar Luiz; Nunes, Vania dos Santos [UNESP] (Archives of Endocrinology and Metabolism, 2016)
We conducted a systematic review and meta-analysis of randomized and non-randomized controlled trials that compared pure endoscopic with microscopic transsphenoidal surgery (TSS) in the resection of pituitary tumors. Embase, PubMed, Lilacs, and Central Cochrane were used as our data sources. The outcomes were total tumor resection, achievement of biochemical control of functioning adenomas, hospital stay and surgery complications. The randomized trials were analyzed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Two randomized and three prospective controlled non-randomized studies were included. Two studies, including 68 patients, evaluated total tumor resection and the meta-analysis did not show differences between the groups [RR: 1.45 (95% CI: 0.87, 2.44)]. Three studies involving 65 patients analyzed the achievement of biochemical control and no statistical difference was found [RR: 0.94 (95% CI: 0.7, 1.26)]. All five studies compared the frequency of postoperative complications between intervention and control group and meta-analysis favored for a low rate of postoperative complications in the endoscopic TSS group [(RR: 0.37 (95% CI: 0.16, 0.83)]. Due to the low evidence level and low number of observations, the results of our meta-analysis should not be viewed as a final proof of inferiority or superiority of one approach in relation to the other. More data including higher numbers of observations are needed.
Keywords: Neurosurgical procedure; Pituitary tumor; Review; Surgical endoscopy; Systematic